2016
DOI: 10.4048/jbc.2016.19.4.349
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Taurine-Upregulated Gene 1 Promotes Cell Proliferation by Inhibiting MicroRNA-9 in MCF-7 Cells

Abstract: PurposeThis study was designed to investigate the role of taurine-upregulated gene 1 (TUG1) in MCF-7 breast cancer cells and the molecular mechanism involved in the regulation of microRNA-9 (miR-9).MethodsThe expression of TUG1 in breast cancer tissues and cells was evaluated using quantitative reverse transcription polymerase chain reaction. Cell viability was examined using a 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay; cell cycle progression and apoptosis were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Our study also explores the underlying mechanism of DSCAM-AS1 in the modulation of target miRNA. DSCAM-AS1 regulates (Zhao & Ren, 2016). These previous findings all reveal the important interplay between lncRNAs and miRNAs in the regulation of multiple cancer cells.…”
Section: Discussionsupporting
confidence: 55%
“…Our study also explores the underlying mechanism of DSCAM-AS1 in the modulation of target miRNA. DSCAM-AS1 regulates (Zhao & Ren, 2016). These previous findings all reveal the important interplay between lncRNAs and miRNAs in the regulation of multiple cancer cells.…”
Section: Discussionsupporting
confidence: 55%
“…[25][26][27] In the current study, we observed an elevation of TUG1 levels in RCC cell lines compared with the normal kidney cells, and overexpression of TUG1 in RCC tumors compared with the matched adjacent normal tissues. 22,30 The role of miR-9 in cancer progression was controversial. 11 Using siRNA knockdown, our functional study demonstrated that TUG1 could promote both cell proliferation and cell migration in RCC cells, which was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…22 Interestingly, miR-9 levels were remarkably decreased in RCC tumor tissues compared with normal tissues ( Figure 4A). We reviewed several studies on miRNAs regulated by TUG1 and analyzed their expression in RCC tumor tissues.…”
Section: Tug1 Negatively Regulated Mir-9 In Rcc Cellsmentioning
confidence: 96%
“…Oncogenic function Glioma (53) miRNA sponge (miR-144) Glioma (9) Recruitment of PRC2, miRNA sponge (miR-145) Glioma (54) miRNA sponge (miR-26a) Glioma (55) miRNA sponge (miR-299) Oral squamous cell carcinoma (56) Unknown Esophageal squamous cell carcinoma (57,58) Unknown Cervical cancer (59) Unknown Small cell lung cancer (60) Recruitment of PRC2 Gastric cancer (61) miRNA sponge (miR-144) Gastric cancer (62) Recruitment of PRC2 Hepatocellular carcinoma (63) Recruitment of PRC2 Hepatoblastoma (64) miRNA sponge (miR-34a) Gallbladder carcinoma (65) miRNA sponge (miR-300) Breast cancer (66) miRNA sponge (miR-9) Breast cancer (67) Unknown Colorectal cancer (68)(69)(70) Unknown Ovarian cancer (71) Unknown Renal cell carcinoma (72) Unknown Bladder cancer (49) Unknown Bladder cancer (48) miRNA sponge (miR-145) Bladder cancer (73) Unknown Osteosarcoma (50) Unknown Osteosarcoma (74) miRNA sponge (miR-9) Osteosarcoma (75) miRNA sponge (miR-335) Tumor-suppressive function Cervical cancer (46) Recruitment of PRC1 and PRC2 Non-small-cell lung carcinoma (51,76)…”
Section: Cancer Type Molecular Functionmentioning
confidence: 99%